Implementation of Total Quality Management in Improving The Performance of Job Training Institutions (LPK) Takemura Indonesia, Bandung Regency - Iis Istikomah; Ifa Shahrash (Advanced Qualitative Research, 2026)
This study is motivated by the fluctuating number of participants at LPK Takemura Indonesia, Bandung Regency, and the urgent need to improve its quality management system in order to compete in the digital era and meet industry requirements. The purpose of this research is to examine how the implementation of Total Quality Management (TQM) can enhance the performance of LPK Takemura, particularly in terms of sales (training participant enrollment), customer satisfaction, and internal institutional management. This study employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. Informants were selected using purposive sampling, involving the founder, director, administrative staff, and active training participants. The findings indicate that most TQM principles have been implemented at LPK Takemura, including customer focus, employee involvement, and continuous improvement. This implementation has positively impacted institutional performance, especially in increasing the number of participants (sales), improving customer satisfaction, and strengthening internal management. Moreover, the integration of a gender perspective in training contributes to women’s empowerment, promotes inclusive entrepreneurship, and fosters a more equitable and participatory work environment. The implementation of TQM is proven not only to improve the institution’s sales performance but also to generate broader social and economic implications.